(untitled) («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
This article is devoted to translation, translation problems and translation theory, which is one of the current problems. The article presents the opinions of various scholars about translation.